The quality of audit opinion does not affect the level of corruption in the East Java provincial government - Moch. Alfa Dholi; Sri Pujiningsih; Ani Wilujeng Suryani (Universitas Negeri Malang, 2023)
Abstract This study aims to analyze the role of the Audit Board of Indonesia (BPK) in reducing and preventing corruption in the local government. The focus of the research discussion is the case of corruption that occurred in the 2016-2018 period. The data came from the regional government of East Java Province, which consists of 9 cities and 29 regencies, based on the number of corruption cases and BPK audit results in each area. The independent variable used was the results of the BPK audit on the Regional Government of East Java Province, which consisted of audit findings and audit opinions. The dependent variable was the level of corruption in the East Java regional government handled by the Attorney General's Office. This study used a panel data regression analysis model. The results of the study showed that audit opinions and BPK audit findings had no significant effect on the level of corruption cases in the regional government of East Java Province.AbstrakPenelitian ini bertujuan untuk menganalisis peran BPK dalam mengurangi dan mencegah terjadinya korupsi pada pemerintah daerah. Fokus pembahasan penelitian adalah kasus korupsi yang terjadi pada periode tahun 2016-2018. Data berasal pemerintah daerah Provinsi Jawa Timur yang terdiri dari 9 kota dan 29 kabupaten, berdasarkan jumlah kasus korupsi dan hasil audit BPK pada setiap masing-masing daerah. Variabel independen yang digunakan adalah laporan hasil audit BPK pada Pemerintah Daerah Provinsi Jawa Timur yang terdiri dari temuan audit dan opini audit. Variabel dependen adalah jumlah korupsi pemerintah daerah Jawa Timur yang ditangani oleh Kejaksaan. Penelitian menggunakan model analisis regresi data panel. Hasil penelitian menunjukkan bahwa opini audit dan temuan audit tidak berpengaruh signifikan terhadap tingkat kasus korupsi di pemerintah daerah Provinsi Jawa Timur.